(untitled) (Journal of actual problems of jurisprudence, 2019)
This article is devoted to the actual date on the protection of the rights of children deprived of parental care and the rationale that foster care can provide their family environment and upbringing. Keywords: foster education; children deprived of parental care; protection of the rights of children; form of the device of children.